Spanish Versions of the Outcome Rating Scale and the Session Rating Scale: Normative Data, Reliability, and Validity - Andrade-González, Nelson; Rodrigo-Holgado, Irene; Fernández-Rozas, Jesús; Cáncer, Pablo F.; Lahera, Guillermo; Fernández-Liria, Alberto; Rubio, Gabriel; Miller, Scott D. (Frontiers in Psychology, 2021)
Routine Outcome Monitoring (ROM) uses standardized measures to both track and inform mental health service delivery. Use of ROM has been shown to improve the outcome of psychotherapy when applied to different types of patients. The present research was designed to determine the reliability and validity of the Outcome Rating Scale (ORS) and the Session Rating Scale (SRS) in a sample of Spanish patients. After a controlled process of translation into the Spanish that is spoken and written in Spain (i.e., in Europe, as distinct from, e.g., Latin American Spanish), both measures were completed by patients of an outpatient mental health unit during eight sessions of psychotherapy. Sixty mental health patients filled out the ORS and 59 the SRS. In addition, the ORS was completed by 33 people who constituted the non-clinical sample. The cut-off of the ORS was 24.52 points, and the Reliable Change Index was 9.15 points. ORS and SRS scores exhibited excellent internal consistency. The temporal stability of the SRS was adequate. The convergent and discriminant validity of the two measures were adequate. Regarding the factorial validity of the ORS and the SRS, in the third psychotherapy session, confirmatory factor analyses evidenced the existence of a unifactorial model. The predictive validity of SRS was acceptable. The ORS was sensitive to changes in patients’ symptoms. In conclusion, compared to the original English versions of the ORS and SRS measures, the Spanish versions of the measures are also reliable and valid.